2017
DOI: 10.1002/jcph.884
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Nusinersen in the Cerebral Spinal Fluid and Plasma of Pediatric Patients With Spinal Muscular Atrophy Following Intrathecal Administrations

Abstract: Nusinersen is an antisense oligonucleotide intended for the treatment of spinal muscular atrophy. The pharmacokinetics of nusinersen, following intrathecal administrations, in the cerebrospinal fluid (CSF) and plasma of 72 pediatric patients (3 months to 17 years) with spinal muscular atrophy across 5 clinical trials was analyzed via population-based modeling. With sparse data in the CSF and profile data in the plasma, a linear 4-compartment model simultaneously described the time-concentration profiles in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 23 publications
0
61
0
1
Order By: Relevance
“…Recently, nusinersen, a novel intrathecal therapeutic agent for spinal muscular atrophy was introduced . However, because there were no previous studies describing the spinal CSF volume of pediatric patients, age‐based dose scaling of nusinersen trials were determined based on the age‐to‐brain CSF volume relationship reported by Matsuzawa et al Thus, along with the brain CSF volume, the spinal CSF volumes in the present study can be used for a more accurate prediction of the total CSF volume in pediatric patients. However, other factors such as the fluid dynamics of CSF, lipid solubility and baricity, and the drugs themselves must be considered to understand the pharmacokinetics and pharmacodynamic characteristics of intrathecal medication…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Recently, nusinersen, a novel intrathecal therapeutic agent for spinal muscular atrophy was introduced . However, because there were no previous studies describing the spinal CSF volume of pediatric patients, age‐based dose scaling of nusinersen trials were determined based on the age‐to‐brain CSF volume relationship reported by Matsuzawa et al Thus, along with the brain CSF volume, the spinal CSF volumes in the present study can be used for a more accurate prediction of the total CSF volume in pediatric patients. However, other factors such as the fluid dynamics of CSF, lipid solubility and baricity, and the drugs themselves must be considered to understand the pharmacokinetics and pharmacodynamic characteristics of intrathecal medication…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, we calculated both LS‐CSF volume and TLS‐CSF volume in pediatric patients for the first time. As LS‐CSF volume is one of the most important factors during spinal anesthesia and TLS‐CSF volume can be used to assess the pharmacokinetics of intrathecal medications, the results from this study will be helpful in understanding these issues of pediatric intrathecal medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, the apparent volume of distribution in the CSF was estimated for nusinersen using a population PK analysis . The estimate was greater than the CSF volume, suggesting significant distribution into CNS tissues.…”
Section: Translational Strategies Encompassing Preclinical Evaluationmentioning
confidence: 99%